REGIONAL DIFFERENCES IN THE LEVEL OF TOURISM DEVELOPMENT IN THE RUSSIAN FEDERATION - Elena G. KROPINOVA; Tatiana Y. KUZNETSOVA; Gennady M. FEDOROV (Geo Journal of Tourism and Geosites, 2020)
This article presents an analysis of the level of tourism development across the Russian Federation. The study explores Russian regions by considering the key characteristics of tourism: the number of accommodation facilities, international visitors staying in accommodation facilities, the number of people employed in tourism and hospitality, and the value added created by these sectors of economy. An aggregate index is used to assess levels of tourism and recreation development and compare administrative units on this measure. An original methodology is employed to track shifts in Russian tourism, identify regions specialising in tourism, and forecast tourism development at a regional level.